Numerical approach for the prediction of formation and hydraulic fracture properties considering elliptical flow regime in tight gas reservoirs - Hossain, Mofazzal; Al-Fatlawi, O.; Brown, D.; Ajeel, M. (2018)
© 2018, Offshore Technology Conference. As tight gas reservoirs (TGRs) become more significant to the future of the gas industry, investigation into the best methods for the evaluation of field performance is critical. While hydraulic fractured well in TRGs are proven to be most viable options for economic recovery of gas, the interpretation of pressure transient or well test data from hydraulic fractured well in TGRs for the accurate estimation of important reservoirs and fracture properties (e.g. fracture length, fracture conductivity, skin and reservoir permeability) is rather very complex and difficult because of the existence of multiple flow profiles/regimes. The flow regimes are complex in TGRs due to the large hydraulic fractures near the wellbore, combined with low matrix permeability and reservoir heterogeneity; and consequently the interpretation of well test or pressure transient data using the classical approaches usually used for conventional reservoirs can produce wrong results with high level of uncertainties. In addition, the time required to achieve radial flow regimes for such tight reservoir, as key condition to use classical approaches, is impractically long and not feasible from the context of both economic and practical operation viewpoint. These inherent causes and the operating limitations require amendment of the well test technique to analyse linear or elliptical flow regimes to accurately estimate the reservoir and fracture properties. This paper proposed a simplified numerical approach to predict the reservoir and fracture parameters based upon well test or production data from hydraulic fractured vertical well in tight gas reservoir considering elliptical flow regime. Emphases are given on the development of simple computation tool that can be used as a handy, efficient and accurate tool to supplement the need for commercial simulators; yet can provide with estimation of reservoir and fracture properties with high level of accuracy especially in the case when limited pressure transient data is available.